(untitled) (mathematica didactica, 2026)
Previous studies provided a catalogue of the mathematical learning prerequisites that are regarded necessary for incoming STEM freshmen from the perspective of university instructors. The present study elicited 92 expert teachers’ views on how well these prerequisites 1) can be addressed by school mathematics education (implemented curriculum) and 2) are available in high school graduates (realized curriculum). We found that expert teachers regarded most of the prerequisites addressable by school mathematics education. In contrast, they indicated that only a few aspects are actually completely available to at least 50% of the high school graduates.